Stock Management Optimization as a Sales Forecasting Strategy in Ayam Geprek SMEs - Trianawati, Lukie; Lidya, Leni; Fatimah, Ai Imas Faidhoh; Suhaima, Nurafi Razna; Fajri, Aulia Irhamni (PT FORMOSA CENDEKIA GLOBAL, 2024)
Forecasting predicts future sales volumes and is essential for efficient stock management in businesses like ayam geprek, which relies on fresh ingredients. Discrepancies between production and demand can lead to excess inventory, increased costs, and losses. This study employs a quantitative approach, analyzing September 2024 sales data using judgment sampling and methods like Moving Averages and Exponential Smoothing (ETS). Data processing includes error evaluation (MAD, MSE, MAPE) to identify the best forecasting method. Results show ETS with α = 0.5 is optimal, achieving the lowest error rates (MAD: 6, MSE: 73, MAPE: 15%). These findings help entrepreneurs improve inventory strategies, reducing risks of shortages or surpluses